OPTIMIZING CAMPUS PROMOTION STRATEGIES: A STUDY ON SELECTING POTENTIAL PROVINCES USING THE AHP METHOD - Ega Adrianto; Karina Amanda Larasati; Henry Dwi Prihartanto (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2026)
Yogyakarta is recognized as a national education hub in Indonesia, characterized by intense competition among higher education institutions, which necessitates data-driven strategic enrollment management (SEM) approaches. This study aims to identify and prioritize potential provinces for campus promotion using the Analytic Hierarchy Process (AHP) as a multi-criteria decision-making method. Four academic performance–based criteria—Grade Point Average (GPA), study duration, student achievement, and bachelor’s thesis performance—were evaluated across four provinces: West Kalimantan, East Nusa Tenggara (NTT), West Nusa Tenggara (NTB), and East Kalimantan. Pairwise comparisons and consistency testing were applied to ensure reliable weighting and ranking. The results indicate that GPA is the most influential criterion, followed by study duration, student achievement, and bachelor’s thesis performance. Based on the overall priority scores, West Nusa Tenggara ranked first (1.213), followed by East Nusa Tenggara (0.748), West Kalimantan (0.407), and East Kalimantan (0.229). These findings demonstrate that integrating academic outcome indicators with geographic prioritization provides a systematic and objective basis for targeted promotion planning, supporting more effective and sustainable student recruitment strategies.